(untitled) (Scripta Theologica, 2017)
There are three main ways in which Christian theology enriches a broader scientific narrative. First, it provides us with a reassurance of the coherence of reality; second, it offers answers to the scientifically unanswerable ultimate questions; and third, it is able to enrich a scientific narrative by preventing it from collapsing into a technocratic catalogue of common things. In this regard, the paper explores some aspects of the relevance of theology for the understanding of the world, as a means of opening up a discussion of how could be developed an inclusive scientific theory.